Penerapan Model Pembelajaran Kooperatif Tipe Bamboo Dancingdalam Meningkatkan Hasil Belajar IPS : Penelitian Tindakan Kelas di Kelas VII-5 MTSN 11 Jakarta - Sukma Islamiani, Gemilang; Fatgehipon, Abdul Haris; Yuliani, Shahibah (Edukasi IPS, 2019)
This research aims to determine if the application of the Cooperative learning model type Bamboo Dancing can improve the learning outcomes of IPS. This study was conducted on class VII-5 which amounted to 32 students at MTsN 11 Jakarta in the second semester of the 2018/2019 from March to May 2019. The method used in this research is the classroom action research that use three cycles, each of which consists of four stages : planning, acting, observing and reflection. Based on the results of research from learning outcomes there is an increase in each of cycle. In the first cycle 1 of 47% (15 students) reached a score above KKM 73 with an average of 68 learning outcomes, In  cycles 2 of 72% (23 students) reached a score above KKM 73 with an average of 76 learning outcomes, and In cycle 3 of 84% (27 students) reached a score above KKM 73 With an average value of 83 learning outcomes. In addition to increased learning outcomes, the activity of learners has also increased on each of its cycle based on the ability to asking, answering, arguing and collaborate. It can be concluded that the implementation of the Cooperative learning model type Bamboo Dancing can improve the learning outcomes of learners and can improve the learner activity, so that learners can get better IPS learning outcomes that are above KKM 73.